Use of Pyrophosphate Labelled with 99mTc in the Scintigraphic Diagnosis of Myocardial Infarction - Kubiček, J.; Vižda, J.; Duška, F. (Nuklearmedizin - NuclearMedicine, 1977)
Scintigraphy of acute myocardial infarction 1 hr after intravenous administration of pyrophosphate labeled with 99m Tc suitably complements the classical diagnostic methods. A delay longer than that does not improve the quality of the scan. An acute lesion can be detected within 24 hours to 1 week after its development.